The prognostic value of the number of harvested negative lymph nodes in patients treated by esophagectomy with or without neoadjuvant chemoradiation - Brunner, Maximilian; Merkel, Susanne; Krautz, Christian; Kersting, Stephan; Grützmann, Robert; Weber, Georg (Anticancer Research, 2020)
Background/Aim: The prognostic value of the number of harvested negative lymph nodes (NLNs) in patients with node-negative esophageal carcinoma treated by esophagectomy with or without neoadjuvant chemoradiation is unclear. Patients and Methods: A total of 136 patients who underwent oncological esophagectomy with two-field lymphadenectomy from 1995 to 2014 were analyzed regarding the prognostic impact of NLNs. 86 patients received primary surgery (group 1) and 50 patients had preoperative chemoradiation followed by surgery (group 2). Results: The 5-year overall survival (OS) was 61.1%. Median lymph node harvest was significantly higher in group 1 (39 vs. 34 in group 2, p=0.007). In group 1, patients with a higher number of negative lymph nodes (>40) had a better OS [57.6% vs. 78.9%, HR=0.5 (0.3-0.9), p=0.026], whereas there was no significant difference in group 2 using the same cutoff (47.6% vs. 66.7%, p=0.476). Conclusion: The number of NLNs is an independent prognostic factor for patients with esophageal carcinoma treated by primary esophagectomy, but not in patients after neoadjuvant chemoradiation.
CRIS-Team Scopus Importer:2020-05-15
Keywords: Esophageal carcinoma; Lymphadenectomy; Neoadjuvant chemoradiation; Oncological esophagectomy; Prognosis; Survival